2017
DOI: 10.1515/afpuc-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhaled and oral n-acetylcysteine on airway defense mechanism

Abstract: Aim:N-acetylcysteine is the prototype of mucolytic agents. The aim of this study was to evaluate the acute and chronic effect of inhaled and oral N-acetylcysteine on airway reactivity, cough reflex and ciliary beat frequency and parameters of mentioned defense mechanisms were assessed in physiological conditions.Methods:An experiment was performed using healthy guinea pigs treated with inhaled (0.6 M; 5min) and oral N-acetylcysteine (20 mg/kg), administrated either acutely as a single dose or chronically durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…18 In a study by Pappová et al showed that nebulization with Nacetylcysteine caused bronchospasm by increasing airway reactivity. 19 Similarly, in our study nebulization with both 3% hypertonic saline and N-acetylcysteine caused increased airway reactivity and rhonchi. We recommend further research in this regard.…”
Section: Discussionsupporting
confidence: 79%
“…18 In a study by Pappová et al showed that nebulization with Nacetylcysteine caused bronchospasm by increasing airway reactivity. 19 Similarly, in our study nebulization with both 3% hypertonic saline and N-acetylcysteine caused increased airway reactivity and rhonchi. We recommend further research in this regard.…”
Section: Discussionsupporting
confidence: 79%
“…11 Our research of the positive effects of a 10-day NAC treatment with a nebulizer, such as reducing disease symptoms, improving quality of life, and reducing the severity of bronchial obstruction, generally coincides with previous studies, although they were performed in a different contingent of patients with a pulmonary profile. Interestingly, similar to our results for cough reduction after NAC treatment were obtained in one of the experimental studies, 31 which researched the effect of the drug on the protective mechanisms of respiratory tract in animals. The argument for the use of NAC with a nebulizer can be connected to the higher potential of its mucolytic action during direct contact with mucus, which due to the presence of a sulfhydryl group in the molecule.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, less risk for exacerbations of chronic bronchitis or chronic obstructive pulmonary disease (COPD) has been recently confirmed in patients taking mucolytics probably due to reduced mucus viscosity making it easier to expectorate (Poole et al, 2019). Mucolytics provide also additional direct cilio-stimulatory and bronchodilator effects without impact on the cough sensitivity, anti-inflammatory (Pappova et al, 2017;Frañováet al, 2019), antioxidant (Miyake et al, 1999) or immunomodulatory properties, in addition to the ability to reduce bacterial adhesiveness (Braga et al, 1999, Pappová et al, 2018.…”
Section: Cilia In Mucociliary Clearancementioning
confidence: 98%
“…The mucokinetic agents may influence mucociliary clearance directly by acting on the cilia. There is evidence that bronchodilators SABA and LABA improve beating kinematics via increase in the CBF in in vitro conditions (Devalia et al, 1992;Kanthakumar et al, 1994;Frohock et al, 2002;Pappova et al, 2017). However, in patients with moderate and severe bronchial asthma, the CBF significantly declines despite treatment with long-acting bronchodilators (Thomas et al, 2010).…”
Section: Other Drugs With Cilio-stimulatory Properties (Mucokinetics)mentioning
confidence: 99%